ALLELOPATHIC PLANT WATER EXTRACTS TANK MIXED WITH REDUCED DOSES OF ATRAZINE EFFICIENTLY CONTROL TRIANTHEMA PORTULACASTRUM L. IN ZEA MAYS L. - M. B. Khan; M. Ahmad; M. Hussain; K. Jabran; S. Farooq; M. Waqas-Ul-Haq (Journal of Animal and Plant Sciences, 2012)
Environmental pollution, development of herbicidal resistance among weeds and health hazards due to non judicious use of herbicides has forced the researchers to make concerted efforts to develop alternate weed control strategies. In that scenario, use of allelopathic plant water extracts with reduced rates of herbicides to control weeds in arable crops has become an attractive option for the researchers. The present study was conducted to investigate the possible effects of allelopathic plant water extracts in combination with reduced doses of atrazine for weed control in maize. Atrazine was applied @ full dose (500 g a.i. ha-1), ½ dose (250 g a.i. ha-1), ⅓ dose (167 g a.i. ha-1) and ¼ dose (125 g a.i. ha-1) alone; reduced doses (½, ⅓ and ¼) of herbicide were applied in combination with 20 L ha-1 of allelopathic plant water extracts of sorghum, brassica, sunflower and mulberry; 20 L ha-1 of allelopathic plant water extracts of sorghum, brassica, sunflower and mulberry was applied alone;  while weedy check was also maintained as control. The four levels of atrazine showed 65-81% suppression of weeds density and weeds dry weight over control (weedy check), while allelopathic plant water extracts showed 70-75% suppression of weeds density and dry weight when used in combination with half and 1/3rd dose of atrazine over control. Nonetheless, 49%, 36% and 31% more grain yield was obtained where full dose (alone) and half and ⅓ dose of atrazine in combination of allelopathic plant water extract were applied, respectively over control. In conclusion, allelopathic plant water extracts can be utilized with reduced doses of herbicide to keep environment healthy and efficient weed control in maize. Formulation of allelopathic water extracts into a handy product would facilitate their use for environment friendly weed management.
Keywords: allelopathy; atrazine; herbicide reduction; maize; mulberry; weeds control.